Peran Hamba Tuhan Dalam Membina Jemaat GKSI Eklesia Kelempu Tentang Pentingnya Hubungan Dengan Tuhan dan Sesama - Adrianus Ama Kii; Ester Katrina Tinambunan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Relationships with God and others are the most important things in a Christian's life. However, in practice, many GKSI Eklesia Kelempu congregations are not yet fully aware of or able to live up to this principle. They may be faithful in worship, but their relationship with God is only a formality, without deep appreciation. On the other hand, relationships with others are often characterized by conflict, prejudice, or lack of concern. This challenge is also exacerbated by the GKSI Eklesia Kelempu congregation's lack of understanding of the importance of building a balanced spiritual life. The research method uses qualitative, observation-based research by looking at phenomena that occur and carrying out activities directly. Next, collect data through feedback observations. And finally, after the observation data is collected, it will be processed into writing. The results of the findings of this research show positive changes in the spiritual life of the GKSI Eklesia Kelempu congregation, such as being more active in praying, attending worship services, and paying attention and helping each other.